Analisa Pengembangan Sumber Daya Manusia Pada Kursus English Special Training Di Babelan Kabupaten Bekasi - Riga Negara; Djuni Thamrin; Matdio Siahaan (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
English discourages some students from learning better. How is the quality of management in educational institutions English courses. How to make teachers comfortable working in English Special Training (EST) tutors. How to maintain the quality of education. To know the quality of management at the Educational Institution course. To know how to retain teachers in English Special Training (EST) tutoring. To know how to maintain the quality of education In this study, The author will use qualitative research methodology in accordance with the formulation of the problem and the purpose of the study. Therefore, this study will focus on descriptive analysis in the form of narratives with the aim of understanding about HR Development Analysis in English Special Training Course Education. According to (Sugiyono, 2010) qualitative research methods as a philosophically based research approach used in scientific settings (experiments) where researchers play a role As an instrument, data collection methods and qualitative analysis emphasize meaning.